Underlying mechanism of CO2 adsorption onto conjugated azacyclo-copolymers: N-doped adsorbents capture CO2 chiefly through acid–base interaction?. Issue 30 (2nd July 2019) - Qi, Shi-Chao; Wu, Ju-Kang; Lu, Jie; Yu, Guo-Xing; Zhu, Rong-Rong; Liu, Yu; Liu, Xiao-Qin; Sun, Lin-Bing
Abstract : Induction force is demonstrated to account for the improved CO2 adsorption by N-doped sites of adsorbents instead of acid–base interaction. Abstract : The empiricism that extrinsic or doped materials universally perform much better than their intrinsic counterparts has been verified to be feasible in the adsorptive CO2 capture. Thus, a variety of N-doped solid adsorbents are well-engineered to adsorb CO2 . However, the true nature of the N-doped sites in the aggregation state and the underlying mechanism of CO2 adsorption therein are difficult to determine. In the present study, four well-defined azacyclo copolymers with peculiar textural characteristics, uniformly arrays and tunably effective N-doped sites were fabricated to experimentally determine the precise relation between adsorbed CO2 molecules and the N-doped sites incorporated into an adsorbent. With multifaceted quantum chemical computations, induction forces were proven to account for the improved CO2 adsorption on the N-doped sites instead of the conventionally assumed generalized acid–base interaction. The negative electrostatic potentials were demonstrated to be the real cause for improving the CO2 adsorption and a robust indicator for the effectiveness of the N-doped sites. Besides, a precise linear function is proposed to quantitatively describe this subject–object relationship for the first time.